Carbon dots: surface engineering and applications - Liu, Weijian; Li, Chun; Ren, Yanjing; Sun, Xiaobo; Pan, Wei; Li, Yanhua; Wang, Jinping; Wang, Weijun (Journal of materials chemistry. B, Materials for biology and medicine, 2016)
Carbon dots have attracted a great deal of attention because of their high performance, cheap and facile preparation, and potential applications in a wide area. In order to broaden their applications, especially to meet specific requirements, surface engineering, including tailoring surface functional group coating and subsequent chemical modification as required, is an effective strategy for further functionalization of carbon dots. In this article, representative approaches to coating the surface with various functional groups, and strategies for conjugating specific materials onto the surface of carbon dots for functional modification via covalent bonds, electrostatic interactions and hydrogen bonds are highlighted, as well as the results from explorations of their various applications in target modulated sensing, accurate drug delivery and bioimaging at high resolution.